Ecological Studies of the Evergreen Forests of Matheran. I. Floristic composition - Satyanarayan, Y.; Mudaliyar, M. S. (Indian Forester, 1959)
A brief review of literature on the geology, soils, climate and floristic composition of the evergreen forests of Matheran is presented. A preliminary survey of these forests was made according to modern methods of plant ecology. Data regarding certain analytical characters such as frequency, density, relative density, dominance, and percentage dominance are recorded and the results compared with the numerical percentage data given in the Working Plan. It is shown that Memecylon edule is not the type species of these forests which are codominated by Eugenia jambolana and Eugenia heyneana. The increase in dominance and density of some species and the decrease in the numbers of other species are shown. The paucity of individual species in the higher size classes and the reduction in the dominance of certain species are attributed to intense biotic factors. Similar ecological studies of the various forest types of India are suggested to assesss accuractely their floristic composition in relation to ecological factors.